Experience with the use of trastuzumab deruxtecan in real-world clinical practice: data from Clinical Oncology Dispensary no. 1 (Krasnodar) and Federal Scientific Clinical Center of the fMBA of Russia - M. Yu. Mostovoy; S. V. Sharov; E. V. Lymar; A. G. Onishchenko; J. A. Bat; A. S. Melnikova; G. G. Lisachenko; A. G. Kedrova; T. A. Greyan (Academy for Practical Oncology, 2026)
This article presents a systematic review of international and domestic experience with the use of trastuzumab deruxtecan in patients with HER2-positive and HER2-low metastatic breast cancer. Based on an analysis of key registration studies (DESTINY-Breast01, -03, -04), and confirmatory clinical trials (DESTINY-Breast02, -12) and real-world clinical practice data from the Clinical Oncology Dispensary No. 1 (Krasnodar) (n = 22) and Federal Scientific Clinical Center of the Federal Medical and Biological Agency of Russia (n = 6), the article summarizes the specifics of drug administration in the Russian healthcare setting, its efficacy profile, and manageable toxicity. A clinical case of a patient with HER2-positive mBC and brain metastases is described in detail, demonstrating long-term disease control (more than 15 months) with trastuzumab deruxtecan therapy in the second line after progression during treatment with a combination of trastuzumab, pertuzumab, and docetaxel. Practical recommendations for clinicians on monitoring the key adverse event – interstitial lung disease and pneumonitis – have been formulated.